Meander bowtie Antenna for Wearable Application - N. Othman; N. A. Samsuri; M. K. A. Rahim; K. Kamardin; H. A. Majid (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This paper proposes a flexible compact bowtie antenna for medical application that operates at 2.45 GHz. The proposed antennas are miniaturized using meander technique. Both substrates and conducting material of the antenna are made of flexible material semi-transparent film as the substrate and shieldit fabric as the conducting material which suitable for wearable and on body application. The results show that the total length of the antenna is significantly reduced by up to 38%. However, the gain of the antenna is slightly decreased when the size of the antenna become smaller. The results of this research could provide guidance and has significant implication for future development of wearable electronics especially in medical monitoring application.